The hafnium-neodymium isotopic composition of Atlantic seawater - Rickli, J; Frank, M; Halliday, A (2009)
The first full water column hafnium isotopic compositions of Atlantic seawater have been obtained at seven locations from the Labrador Sea to the Drake Passage. Despite subpicomolar concentrations in seawater, a precision of the Hf isotopic measurements of < 0.7 εHf units was achieved. An overall εHf range between - 3.1 in the Labrador Sea and + 4.4 in Antarctic bottom water was determined, the distribution of which broadly reflects continental weathering inputs. Within particular water column profiles, significant differences of up to 4 εHf units occur. Combined with Nd isotope data of the same samples, it is evident that the Hf isotopic composition of seawater is too radiogenic for a given Nd isotopic composition and that the largest difference between expected and measured Hf isotopic compositions in seawater occurs near the oldest continental crust in the Labrador Sea. This corroborates the previous proposition, which was mainly based on ferromanganese crust data, that the Hf isotopic composition of seawater is controlled by incongruent weathering of continental crust and possibly, to some extent, by hydrothermal contributions. Hafnium concentrations in the ocean do not increase along the deep ocean conveyer indicating an oceanic residence time of only a few hundred years, which is significantly shorter than previously assumed. The Hf isotopic composition of past seawater can therefore serve as a proxy for short distance, basin scale mixing processes and the regime and intensity of nearby continental weathering processes. © 2009 Elsevier B.V. All rights reserved.